Reconstruction of chromosome rearrangements between the two most ancestral duckweed species Spirodela polyrhiza and S. intermedia - Hoàng, Thị Như Phương (2022)
The monophyletic duckweeds comprising five genera within the monocot order Alismatales are neotenic, free-floating, aquatic organisms with fast vegetative propagation. Some species are considered for efficient biomass production, for life stock feeding, and for (simultaneous) wastewater phytoremediation. The ancestral genus Spirodela consists of only two species, Spirodela polyrhiza and Spirodela intermedia, both with a similar small genome (~160 Mbp/1C). Reference genome drafts and a physical map of 96 BACs on the 20 chromosome pairs of S. polyrhiza strain 7498 are available and provide useful tools for further evolutionary studies within and between duckweed genera. Here we applied sequential comparative multicolor fluorescence in situ hybridization (mcFISH) to address homeologous chromosomes in S. intermedia (2n = 36), to detect chromosome rearrangements between both species and to elucidate the mechanisms which may have led to the chromosome number alteration after their evolutionary separation. Ten chromosome pairs proved to be conserved between S. polyrhiza and S. intermedia, the remaining ones experienced, depending on the assumed direction of evolution, translocations, inversion, and fissions, respectively. These results represent a first step to unravel karyotype evolution among duckweeds and are anchor points for future genome assembly of S. intermedia.